Improving the efficiency of the electrocoagulation process for Palm Oil Mill effluent: A case study in POME processing in a palm oil processing factory in Meulaboh, West Aceh Regency - Daudsyah Muhammad; Mulyati Sri; Rosnelly Cut Meurah; Ambarita Aulia Chintia (BIO Web of Conferences)
Palm oil mill effluent (POME) is a by-product of palm oil processing, which poses a significant risk to environmental integrity due to its high production volume and pollutant content. Therefore, this research offers the POME treatment process using electrocoagulation, a case study in a palm oil processing factory in Meulaboh, West Aceh Regency. Specifically, this study aims to investigate the effect of voltage variation on the removal efficiency of key parameters such as BOD, COD, pH and TSS. The electrode used is made of aluminium (Al) plate with a gap of 2 cm, and the electrolysis time is 60 minutes. The results show that the higher the applied voltage, the greater the parameter removal efficiency, with the best voltage in this result being 25 volts. However, overall, these results have only two parameters that meet wastewater quality standards, which are COD and pH. Further optimization is required to achieve acceptable BOD and TSS levels, highlighting the importance of extended electrolysis times and proper parameter control.